Extracellular Matrix and Cellular Plasticity in Musculoskeletal Development - Ma, Sophia Ka Yan; Chan, Andy Shing Fung; Rubab, Aqsa; Chan, Wilson Cheuk Wing; Chan, Danny (Frontiers in Cell and Developmental Biology, 2020)
Cellular plasticity refers to the ability of cell fates to be reprogrammed given the proper signals, allowing for dedifferentiation or transdifferentiation into different cell fates. In vitro, this can be induced through direct activation of gene expression, however this process does not naturally occur in vivo. Instead, the microenvironment consisting of the extracellular matrix (ECM) and signaling factors, directs the signals presented to cells. Often the extracellular matrix is involved in regulating both biochemical and mechanical signals. In stem cell populations, this niche is necessary for maintenance and proper function of the stem cell pool. However, recent studies have demonstrated that differentiated or lineage restricted cells can exit their current state and transform into another state under different situations during development and regeneration. This may be achieved through 1) cells responding to a changing niche; 2) cells migrating and encountering a new niche; and 3) formation of a transitional niche followed by restoration of the homeostatic niche to sequentially guide cells along the regenerative process. This review focuses on examples in musculoskeletal biology, with concept of ECM regulating cells and stem cells in development and regeneration, extending beyond the conventional concept of small population of progenitor cells, but under the right circumstances even “lineage-restricted” or differentiated cells can be reprogrammed to enter into a different fate.